Answer:
- x = 7 and y = 5 => their sum: 7+5 = 12
- x = -5 and y =-7 => their sum: -5 + (-7) = -12
Explanation:
Let x is the bigger number
Let y is the smaller number
We have:
- The product of two positive numbers is 35
=> xy = 35 (1)
=> x - y = 2
<=> x = y+2 (2)
Substitute (2) into (1) we have:
(y+2) y = 35
<=>
<=> y = 5 or y = -7
When y = 5 we get x = 5+ 2 = 7
When y =-7 we get x = -7 +2 = -5
So we have two possible answers:
- x = 7 and y = 5 => their sum: 7+5 = 12
- x = -5 and y =-7 => their sum: -5 + (-7) = -12